Chronic Urotensin-II Administration Improves Whole-Body Glucose Tolerance in High-Fat Diet-Fed Mice - Chen, Xi; Yin, Lin; Jia, Wei-hua; Wang, Nuo-qi; Xu, Chun-yang; Hou, Bi-yu; Li, Na; Zhang, Li; Qiang, Gui-fen; Yang, Xiu-ying; Du, Guan-hua (Frontiers in Endocrinology, 2019)
Urotensin-II (U-II) is an endogenous peptide agonist of a G protein-coupled receptor— urotensin receptor. There are many conflicting findings about the effects of U-II on blood glucose. This study aims to explore the effects of U-II on glucose metabolism in high-fat diet-fed mice. Male C57BL/6J mice were fed a 45% high-fat diet or chow diet and were administered U-II intraperitoneally for in vivo study. skeletal muscle C2C12 cells were used to determine the effects of U-II on glucose and fatty acid usage as well as mitochondrial respiratory function. In this study, we found that chronic U-II administration (more than seven days) ameliorated glucose tolerance in high-fat diet-fed mice. In addition, chronic U-II administration reduced weight gain and adipose tissue weights, including that of visceral, subcutaneous and brown fat, but without a significant change in blood lipid levels. These were accompanied by increased mRNA expression of the mitochondrial thermogenesis gene Ucp3 in skeletal muscle. Furthermore, in vitro treatment with U-II directly enhanced glucose and free fatty acid consumption with increased aerobic respiration in C2C12 cells. Taken together, chronic U-II stimulation leads to improvement on glucose tolerance in high-fat diet-fed mice and this effect maybe closely related with the reduction in adipose tissue weights and enhancement on energy substrates usage in skeletal muscle.